สภาพการบริหารกิจการนักเรียนของอิสลามวิทยาลัยแห่งประเทศไทย STATE OF STUDENT AFFAIRS ADMINISTRATION OF ISLAMIC COLLEGE OF THAILAND - เพชรนที, สิตาภา; ศิริภิรมย์, วลัยพร (An Online Journal of Education, 2018)
Abstract This research was a descriptive study. The purposes of this research were 1) to study the current and the desirable states of student affairs administration of Islamic College of Thailand, and 2) to study the priority needs for student affairs administration of Islamic College of Thailand. The population of this study was Islamic College of Thailand. The research instrument was using the 5 rating scale questionnaires from total of 123 participants, including 1 school administrators, 2 assistant school administrators and 120 teachers. Which 88.33% of questionnaires were returned. The data was analyzed by frequency, percentage, mean, standard deviation, and PNI. The research finding were as follows; 1) the states of student affairs administration of Islamic College of Thailand overall were also at the high level both on current and desirable basis. The highest mean of the current state was student admission enrollment and orientation work and the lowest mean of the current state was student discipline and behavior work. 2) The priority needs index indicated that the highest needs of student affairs administration of Islamic College of Thailand was student discipline and behavior work ,followed by student development work . Whereas the lowest of the priority needs index was student admission enrollment and orientation work.